A process evaluation of a mobile cooperation intervention: A mixed methods study. (September 2019) - Strandell-Laine, Camilla; Leino-Kilpi, Helena; Löyttyniemi, Eliisa; Salminen, Leena; Stolt, Minna; Suomi, Reima; Saarikoski, Mikko
Abstract: Background: A mobile cooperation intervention was developed to facilitate the cooperation of nursing students with nurse teacher and to improve the students' clinical learning outcomes. The intervention consisted of training in a mobile application's functionality and its use during clinical practicum cooperation procedures. Objectives: To describe the development of a mobile application for student-teacher cooperation and to examine the acceptability of the mobile cooperation intervention for advancing intervention development. Design: A user-centred design and a mobile application development lifecycle model were applied to develop a mobile application. A process evaluation that used mixed methods design was conducted within the intervention group after a randomized controlled trial of a complex mobile cooperation intervention. Setting: The clinical practicum wards of seven hospitals in a hospital district in Finland. Participants: Second-year pre-registration nursing students (N = 52) from one nursing school. Methods: Process evaluation questionnaires were completed upon completion of the five week intervention and essays were written by the students eleven weeks after the intervention ended. Results: A system usability scale (SUS) assessed the overall usability of the mobile application as rather good (a mean SUS score of 69.86 out of 100). Positive feedback about the mobile application's usability and utility was reported and recommendations for further development were highlighted. The intervention demonstrated high acceptability. In general, the students actively used the mobile application for intervention procedures at home and in the clinical practicum ward. Conclusions: The findings support the high acceptability of mobile cooperation intervention and its potential while also providing evidence for the development team's future development of the mobile application. Additionally, this study provides an example of mobile application development and process evaluation in nursing education research.